Clinical efficacy and safety of adjunctive treatment of chronic ischemic heart failure with Qishen Yiqi dropping pills: a systematic review and meta-analysis - Xingmeng, Wang; Guohua, Dai; Hui, Guan; Wulin, Gao; Huiwen, Qu; Maoxia, Fan; Runmin, Li; Lili, Ren (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Our study was to evaluate the effect of Qishen Yiqi Dropping Pills(QSYQ) on the prognosis of chronic ischemic heart failure(CIHF) and its safety.Methods: Databases including CNKI,Wanfang,VIP,CBM,PubMed,Web of Science, The Cochrane Library and EMbase were searched from their inception to April 2023 to screen relevant randomized controlled trials(RCTs). Primary indicators included readmission rates, rates of major adverse cardiovascular events(MACE), and all-cause mortality rates. The quality of the literature was assessed according to the Cochrane Reviewers' Handbook 5.0 and the Modified Jadad Scale (with a score of 4-7 rated as high quality). Meta-analysis was performed using the meta-package created by R software version 4.2.3, continuous data were compared using SMDs, and dichotomous and ordered data were compared using ORs; and the I² test was used to assess the heterogeneity.Results: 59 studies out of 1745 publications were finally included, totaling 6248 patients. Most studies were poorly designed and had some publication bias, with only 26 high-quality papers (Jadad score ≥ 4). Meta-analysis showed that the combined application of QSYQ was able to reduce the readmission rate [OR=0.42, 95% CI (0.33,0.53), P<0.001], all-cause mortality rate [OR=0.43, 95% CI (0.27,0.68), P<0.001], and the incidence of MACE[OR=0.42, 95% CI (0.31,0.56), P<0.001]. Also, the treatment method can improve clinical effectiveness [OR=2.25, 95% CI (1.97,2.58), P<0.001], increase 6-minute walking distance (6MWD)[SMD=1.87, 95% CI (1.33, 2.41), P<0.0001] and left ventricular ejection fraction (LVEF)[SMD= 1.08, 95% CI (0.83, 1.33), P<0.0001], and decrease the Minnesota Living with Heart Failure Questionnaire (MLHFQ) scores [SMD=-2.03, 95% CI (-3.0,-This is a provisional file, not the final typeset article 1.07), P<0.0001], BNP levels [SMD=-2.07, 95% CI (-2.81,-1.33), P<0.0001] and NT-ProBNP levels [SMD=-2.77, 95% CI (-4.90,-0.63), P<0.05]. A total of 21 studies (n=2742) evaluated their adverse effects, of which 13 studies reported no adverse effects and 8 studies reported minor adverse effects.Our results suggest that the combined application of QSYQ can further improve patients' cardiac function and exercise tolerance, improve their quality of life, and ultimately improve patients' prognosis with a favorable safety profile. Nonetheless, limited by the quality and high heterogeneity of the literature, we must be conservative and cautious about the present results.